A study on low‐velocity impact performance of notched GFRP composites repaired by different composite patches: Experiment and modeling. Issue 4 (30th November 2019) - Caliskan, Umut; Ekici, Recep; Yildiz, Ercan; Apalak, M. Kemal
Abstract: Low‐velocity impact performance of notched glass fiber reinforced plastic composites repaired by bonding external composite patches was investigated by experimental and numerical methods. Various patches of different fiber materials such as carbon and glass fiber and thickness were considered under different impact energy levels. The continuum damage mechanics based on a dynamic progressive damage model was using to build the finite element model and cohesive elements were used between the composite patch and notched composite plate. Five different failure criteria based on three‐dimensional Hashin damage models were implemented by the explicit finite element subroutine ABAQUS‐VUMAT with degradation model and used to compare experimental damage areas. The experimental contact force, kinetic energy histories, and experimental damage areas were calculated and compared the numerical ones. While the experimental data confirm the efficiency of the proposed model, they show consistent results with the numerical model. Finally, using the composite patch is succeeded to avoid impact damage. This research provides fundamental support for the appropriate selection of external composite patch type and use of the degradation model with different failure model to achieve high‐efficiency simulation under impact loading.